Peran WHO dalam Menangani Isu Female Genital Mutilation - Damayanthi, Dilla Sri; Putri, Penny Kurnia; Suwecawangsa, Adi P. (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2024)
This study aims to determine the role of the World Health Organization in dealing with the issue of Female Genital Mutilation in Indonesia during the period 2006-2014, to be precise during the emergence of polemics against regulations regarding FGM or female circumcision. The author uses the concept of the role of international organizations as actors who function as norms, makers, ratifiers as well as implementers of regulations, as well as functioning as information, which is analyzed qualitatively. Through secondary data analysis, it was found that WHO, from its inception in 2006 to 2014, had carried out its role and function on the issue of FGM in Indonesia through a resolution WHA61.16 which made Indonesia invite attention to the international stage, thus issuing Minister of Health Regulation No. 6 of 2014. There is a power relationship between WHO and Indonesia, this is in line with the moral authority possessed by WHO, making Indonesia as a member state must follow the rules issued by WHO. WHO provided a statement issued in 1998 which then had an impact on new norms that were born among Indonesian people in 2006-2014. Through regulations, namely Resolution WHA61.16 which has been made and ratified by WHO, in its implementation WHO only comes to observe member countries. Meanwhile, WHO has also carried out its function as information through the release of official FGM guidebooks which are used as references and guidelines for the international community. Keywords: Female Genital Mutilation, World Health Organization, Resolution WHA61.16